Analisis Kesulitan Belajar Siswa dalam Pembelajaran Matematika - Sahabat Halawa; Ratna Natalia Mendrofa; Yulisman Zega; Yakin Niat Telaumbanua (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The factors causing students' learning difficulties are highly varied, including in mathematics education. Learning difficulties refer to the various challenges or barriers individuals face in the learning process, which can impact their ability to acquire, process, and apply knowledge and skills. Due to their diverse nature, these difficulties affect various aspects of the learning process. This study aims to describe the learning difficulties students face, particularly in mathematics education. The sample for this study comprises 25 students, specifically all students in class VIII-B. The data collection methods include tests, interviews, and documentation as supplementary data. The analysis reveals that 48% of the students fall into the